Combined epidural‐general anaesthesia vs general anaesthesia in neonatal gastrointestinal surgery: A randomized controlled trial. Issue 1 (7th October 2019) - Gannam‐Somri, Lina; Matter, Ibrahim; Hadjittofi, Christopher; Vaida, Sonia; Khalaily, Husein; Hossein, Jalaa; Somri, Mostafa
Abstract : Background: Post‐operative ileus is a frequent complication of gastrointestinal surgery under general anaesthesia. The aim of this study was to investigate whether combined epidural‐general anaesthesia is associated with expedited gastrointestinal function recovery in neonates undergoing elective gastrointestinal surgery. Methods: A randomized controlled trial including 60 neonates who underwent gastrointestinal surgery at a university hospital was performed. Thirty neonates received combined epidural‐general anaesthesia (CEGA), and 30 neonates received general anaesthesia (GA) alone. The primary outcome was the post‐operative time to tolerance of full enteral nutrition. The secondary outcomes were the post‐operative time defaecation, the duration of nasogastric drainage, and infections. Results: After excluding two neonates from the CEGA group, where repeated attempts at epidural catheterization were unsuccessful, a total of 58 patients completed the study (CEGA: 28; GA: 30). Full enteral nutrition was tolerated earlier in CEGA vs the GA group (4.0 vs 8.0 days; P  = .0001). Time to defaecation was shorter in the CEGA group (3.5 vs 5.0 days; P  = .0001). Duration of nasogastric drainage was similar between groups (7.0 vs 7.0 days; P  = .9502). Fewer patients in the CEGA group experienced post‐operative infection (35.7% vs 60.0%; P  = .038). Conclusion: Combined epidural‐general anaesthesia is associated with expedited gastrointestinal function recovery and a lower infection risk after gastrointestinal surgery in neonates.